Teledentistry during COVID-19 pandemic: scientometric and content analysis approach - Abdullah Mahdavi; Rasha Atlasi; Roya Naemi (BMC, 2022)
Abstract Introduction During Covid-19 pandemic, people have been reluctant to visit dentist due to the fear of infection. Dentists have also suffered from severe turmoil. Teledentistry has been considered as a key strategy for managing people's oral health. The aim of this study was to investigate teledentistry services in the world during the Covid-19 pandemic and to learn from different experiences. Materials and methods The Web of Science database was searched by scientometric analysis approach, using keywords such as Covid-19, telemedicine, teledentistry and synonymous keywords derived from MeSH. Consequently, 94 articles were extracted from which, 15 articles related to teledentistry during Covid-19 were included in the study, considering the inclusion and exclusion criteria. Results Scientometric analysis and illustration of retrieved articles were performed to identify authors, organizations and countries, and to review cooperation and collaboration networks in this field. Teledentistry was studied during Covid-19 in countries such as China, United States, Japan, Italy and United Kingdom. Types of the software used for communication between dentists and patients were WeChat, BigWord telephone translator, iGAM, WhatsApp, Attend Anywhere (AA), DeRS. The software used for data storage were Mouthwatch TeleDent, and Proforma. For data processing and decision making decision tree algorithms, automated algorithms were employed. Conclusion Teledentistry has the potential to improve the provision of dental services. A fundamental review and careful planning is required to provide such services, particularly in developing countries. Furthermore teledentistry needs more in-depth studies in order to overcome existing and future obstacles and risks while taking advantage of its benefits.